2018
DOI: 10.1371/journal.pone.0191884
|View full text |Cite|
|
Sign up to set email alerts
|

Fungal diversity in oil palm leaves showing symptoms of Fatal Yellowing disease

Abstract: Oil palm (Elaeis guineensis Jacq.) is an excellent source of vegetable oil for biodiesel production; however, there are still some limitations for its cultivation in Brazil such as Fatal Yellowing (FY) disease. FY has been studied for many years, but its causal agent has never been determined. In Colombia and nearby countries, it was reported that the causal agent of Fatal Yellowing (Pudrición del Cogollo) is the oomycete Phytophthora palmivora, however, several authors claim that Fatal Yellowing and Pudrición… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Recently, de Assis Costa et al . 25 analysed the fungal diversity of asymptomatic and symptomatic leaf samples of the oil palm Elaeis guineensis . Here, the fungal community composition in asymptomatic leaves was more similar to each other compared to symptomatic leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, de Assis Costa et al . 25 analysed the fungal diversity of asymptomatic and symptomatic leaf samples of the oil palm Elaeis guineensis . Here, the fungal community composition in asymptomatic leaves was more similar to each other compared to symptomatic leaves.…”
Section: Introductionmentioning
confidence: 99%
“…However, a first report in Thailand revealed that a strain of Pestalotiopsis theae caused a leaf spot disease in oil palm which was further confirmed through pathogenicity test and molecular identification (Suwannarach et al 2013). In a more recent study, the finding of Pestalotiopsis, Neopestalotiopsis, and Pseudopestalotiopsis in oil palm trees cultivated in Brazil revealed that these fungi may cause some lesions to the oil palm leaves although not directly related to serious disease (de Assis Costa et al 2018).…”
Section: Resultsmentioning
confidence: 95%
“…Some studies also looked for possible abiotic causes, with inconclusive results so far [17][18][19]. Recently, techniques such as metabolomics, proteomics, and metagenomics started to be applied to provide insights into the possible FY etiology, initiating a new phase in the process to solve this problem [20][21][22].…”
Section: Introductionmentioning
confidence: 99%